Consequential complications of thrombolytic therapy(TLT) in ischemic stroke - Varahabhatla, Vamsi; Tekwani, Vinisha; Sikorskaya, Marina; Сікорська, Марина Володимирівна (Запорізький державний медичний університет, 2018)
Introduction.Thrombolysis is the most promising therapy for patients with ischemic stroke, although the relative safety of using TLT in different clinical paradigms of acute brain injury (subarachnoid haemorrhage, ischemic stroke) is well documented, experimental data suggest using thrombolytic agents potentiate intracerebral hematomas formation. Objectives. To estimate the risk factors for intracerebral hematomas formation as a complication of TLT. Materials and methods. We analysed 108 case histories (including the observation of 8 patients with intracerebral hematomas) in the period 2007-2017 with the age of the patients in being 32 to 79 years. The analysis included evaluation of the neurological status (according to the NIHSS scale), detailed study of the patient's illness and life history, CT scan, coagulogram in dynamics. All patients received TLT( Actilyse 0.9 mg/kg not exceeding 90 mg) in the period from 3-4,5 hours from the disease onset.
Keywords: тези доповідей